Small and medium enterprise in Oman: key driver to sustainable business performance (Risk-taking) / Nasser Al Yahyaei … [et al.] - Al Yahyaei, Nasser; Husin, Nor Azilah; Supian, Kamisah; Al Hajri, Amer (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
The Sultanate of Oman, one of the Arab Gulf states, looks forward to diversify its sources of income to mitigate the negative impacts of oil price fluctuations on the Sultanate’s economy. In one of its initiatives, the Sultanate focuses on supporting small and medium-sized companies by encouraging Omani to start their own businesses and providing all forms of support. This study is part of a wider study that sheds light on the factors that impact the performance of small and medium enterprises in Oman. The scope of this research paper will be on the impact of risk-taking on the performance of small and medium-sized companies in the Sultanate of Oman. This research employed the quantitative approach in gathering and analysing data using a self-administered questionnaire distributed to owners and business managers of SMEs in Oman. The findings of this study concluded that risk-taking is positively and significantly related to the business performance of SMEs in Oman.